Examining father absence among school students by educational level - Raodatul Adawiyah; Henny Idreswari; Khairul Bariyyah (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2026)
This study aims to identify the profile of fatherless in students based on the level of father involvement in parenting. This study used a quantitative approach with a descriptive design. The sample consisted of 103 junior high and high school students in Makassar City, selected through purposive sampling. Data collection was conducted using the Father Involvement and Father Role in Parenting Scale. Data analysis was conducted descriptively using frequency distributions and percentages to illustrate the level of fatherless among students. The results showed that the majority of students, 77 students (74,75%), fell into the moderate category of fatherless, indicating that father involvement is still present but not optimal. Fourteen students (13,59%) were in the low category, indicating good father involvement, while 12 students (11,65%) were in the high category, indicating low father involvement in parenting. These findings indicate that fatherless among students is at a moderate level, necessitating intervention efforts through guidance and counseling services focused on strengthening family roles, particularly father involvement. This study emphasizes the importance of developing service programs that are responsive to students' family circumstances to support optimal adolescent development in the school environment.